Indústria cultural paulista e seu ecossistema financeiro de sustentação - Sollero, Marcelo de Castro (2022)
This paper aims to map the art and culture funding ecosystem in the state of São Paulo, its structuring role and its relationship with independent production, as well as to analyze the importance of the diversity of funding sources and/or promotion of art and culture in the state of São Paulo for the structuring of the state's cultural productive ecosystem. The value of art and culture in our society is a debate demonstrated by many articles, publications and stakeholders. Through Greg Baeker, David Throsby, Harold Vogel, Patrick Cohendet and David Hesmondhalgh, on the economic issue involved in art and culture, the nature of industry and the complex form of financing that was formed around it was discussed. In order to reach the proposed objective, we will apply a questionnaire for cultural directors and producers, whose results will be analyzed descriptively. In our results, we recognize that the cultural industry in São Paulo is supported by a financing network derived from its high capacity and production complexity. We believe that our research can be applied in the construction of better financing mechanisms in São Paulo and in other states of the federation in favor of strengthening local cultural industries.